Subchronic toxicity of aqueous extract of Alstonia boonei de wild. (apocynaceae) stem bark in normal rats - Nkono Ya Nkono, Barnabé Lucien; Dongmo Sokeng, Selestin; Dzeufiet Djomeni, Paul Désiré; Longo, Frida; Kamtchouing, Pierre (International Journal of Pharmacology and Toxicology, 2015)
Methodology: Wistar rats were randomly assigned into eight groups of five animals each: four male groups and four female groups. Each sex group had a control group receiving distilled water and three test groups receiving 200, 500 and 1000mg/kg respectively. Animal’s body weights were recorded on the first day and once a week for the four experiment weeks. The hematological analysis included total WBC count, total RBC count, Hb, %HCT, MCV, MCH and MCHC. Biochemical/serum profile studies include TG, TC, ALT, AST, urea and TP. Tissue specimens of the liver, kidney and lung were subjected to histological examination using standard hematoxylin-eosin staining.Results: In male rats, aqueous extract showed significant decreases in relative weight of liver with extreme significance P<0.001 at a dose of 200mg/kg (vs. control group), P<0.001 of lung at all the doses, P<0.05 (200 and 500mg/kg) and P<0.01 (1000mg/kg) in heart weight. In relative kidney weight, only the dose of 1000mg/kg showed a significant increase vs. normal control male rats. Unlike male rats, only relative kidney weight in female rats was significantly different from the control group in a dose-dependent manner. The aqueous extract treated male groups showed significant increases P<0.001 (1000mg/kg) of total WBC count and MCHC, significant decreases of %HTC (dose response manner), P<0.05 total RBC count (at doses of 500 and 1000mg/kg) and Hb P<0.01 (500mg/kg) vs. normal male rats. In female rats, the haematological study showed significant increase P<0.01 of total WBC count (at the doses of 500 and 1000mg/kg), significant decreases P<0.05 and P<0.01 of total RBC respectively at the doses of 200 and 1000mg/kg, significant decrease of Hb with extreme significance P<0.001 at the dose 1000mg/kg, %HTC also decrease dose response manner vs. control female rats. Biochemical study showed in male rats significant decreases in level of TG P<0.001 (at the doses of 200 and 500mg/kg) and urea, although it showed any dose-dependent effect vs. control male rats. AST also decreases (P<0.05) in male rats at the dose of 200mg/kg but significantly increase P<0.001 at the dose of 500mg/kg. In the female rats, biochemical study revealed significant increases in level of TG P<0.001 and urea P<0.01 at the dose of 200mg/kg and significant decreases in level of TG P<0.01, AST P<0.05 and urea P<0.05 at the dose of 500mg/kg (vs. control female rats). Microscopically, there were mild hepatic and renal tissue injuries supporting the hematological analysis.Conclusion: The results indicated that aqueous extract of Alstonia boonei De Wild is toxic in high doses.